Pengaruh Konseling Islami terhadap Pembentukan Karakter Siswa di Madrasah - Asyiatul Hamni; Fauziah Anum; Syarifa Ainil Mardiah; Zhafira Muflihah; Hidayani Syam (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Student character development is one of the main goals of education, especially in madrasas based on Islamic teachings. However, there are still many students who have difficulty internalizing Islamic values in their daily lives. This is influenced by a lack of spiritual understanding, weak self-control, and less than optimal guidance methods. Islamic counseling, which is based on the principles of the Qur'an and Hadith, is a relevant holistic approach to strengthen students' Islamic character through the cultivation of spiritual, intellectual, and social values. This study aims to analyze the effect of Islamic counseling on students' character building in madrasah, identify the most affected character aspects, and provide recommendations for integrating Islamic counseling services into the Guidance and Counseling program. Using a qualitative approach with a case study method, the research involved in-depth interviews, participatory observation, and document analysis. Data were collected from students, guidance teachers, and homeroom teachers to explore the experience and impact of Islamic counseling on students' characters, such as honesty, responsibility, discipline, and empathy. The results showed that Islamic counseling is effective in improving student character, especially in terms of self-control and social interaction. The findings support the importance of integrating Islamic counseling services as part of the educational program in madrasah to achieve more optimal character building. This research is expected to contribute to the development of a structured and effective Islamic counseling program.